O trabalho do professor, indicadores de burnout, práticas educativas e comportamento dos alunos: Correlação e predição - da Silva, Nilson Rogério [UNESP]; Bolsoni-Silva, Alessandra Turini [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Capellini, Vera Lúcia Messias Fialho [UNESP] (FapUNIFESP (SciELO), 2015)
The occurrence of burnout in teachers can also affect their educational practices, their repertoire of social skills and the behavior of students. In the literature, such variables are approached independently of each other, which makes it difficult to glean a full understanding of the issue. This study aimed to correlate and predict these variables: teacher working conditions, burnout indicators, educational practices of teachers, student repertoire of social skills and behavior. Ninety four regular education teachers, responsible for classes with students with disabilities or resource classroom who attended an improvement course participated in this study. Data was collected by applying: 1) a Questionnaire about teacher perceptions of the teaching profession; 2) the Maslach Burnout Inventory - MBI; 3) a Questionnaire of Educational Social Skills for Teachers; and 4) a Pro-social Behavior Inventory. Data were analyzed with descriptive statistics (mean and standard deviation), correlation (Spearman test) and linear regression analysis. Results indicated that negative practices influence the level of burnout of teachers, which, in turn, is influenced by working conditions, affecting the emotional health of teachers. The conclusion pointed to the importance of multiple measures to assess work and health of teachers, as well as the need for intervention promoting better working conditions and educational practices.
The work of special education teachers, burnout indicators and behavior of students: Correlations and predictions
Keywords: Burnout; Educative practices; Special education; Teacher health